Black fungi and ants: a genomic comparison of species inhabiting carton nests versus domatia - Yu Quan; Nickolas Menezes da Silva; Bruna Jacomel Favoreto de Souza Lima; Sybren de Hoog; Vania Aparecida Vicente; Veronika Mayer; Yingqian Kang; Dongmei Shi (IMA Fungus)
Abstract Some members of Chaetothyriales, an order containing potential agents of opportunistic infections in humans, have a natural habitat in nests of tropical arboreal ants. In these black fungi, two types of ant symbiosis are known, i.e. occurrence in domatia inside living plants, or as components of carton constructions made of ant-chewed plant tissue. In order to explain differences between strains from these types of association, we sequenced and annotated genomes of two newly described carton species, Incumbomyces lentus and Incumbomyces delicatus, and compared these with genomes of four domatia species and related Chaetothyriales. General genomic characteristics, CYP genes, carbohydrate-active enzymes (CAZymes), secondary metabolism, and sex-related genes were included in the study.